Development and characterization of 16 microsatellites for the Neotropical catfish Pseudoplatystoma reticulatum and cross species analysis - Prado, F. D. [UNESP]; Pardo, B. G.; Guerra-Varela, J.; Senhorini, J. A.; Martinez, P.; Foresti, F. [UNESP]; Porto-Foresti, F. [UNESP] (Springer, 2014)
Sixteen polymorphic microsatellite primers were developed for Pseudoplatystoma reticulatum and provided an efficient multiplex protocol to amplify these loci in four multiplex PCRs. Most microsatellites here obtained showed moderate to high polymorphism levels in P. reticulatum and P. corruscans, as well as interspecific allelic differences, and represents useful genetic markers for population studies in these fishes.
Keywords: Fish genetics; 454 Pyrosequencing; Multiplex-PCR; Genetic diversity